Development of Teaching Materials Based on Local Wisdom in Class IV SDN 056002 LR Worship in Banyumas Village Langkat District - Nurdiyah (Journal of General Education Science, 2024)
This research is development research (Research and Development). Produced a product in the form of local teaching materials based on local wisdom for class IV science and science learning for students at SDN 056002 Lr.Ibadah. This study is because teachers still use teaching materials based on books student or book eye lesson, lack of understanding student towards Rare culture, limitations, lack of innovation in material development teach in school and minimal local teaching materials based on culture school base. In learning IPAS teacher no there is book learning Langkat culture, then teaching materials based on Langkat local wisdom were developed as a companion to teacher books and student books Development Langkat local wisdom-based teaching materials aim to add diversity of teaching materials in learning and to increase knowledge students towards Langkat regional culture. In this study, researchers chose use model Thiagarajan. This model consists of Define, Design, Develop. Subjects used this research involved one class 22 class students IV SDN 056002 Lr. Banyumas Village Worship District. Stabat, Langkat Regency, North Sumatra. The research instrument used a questionnaire sheet which consists of a validation questionnaire for 3 experts and a practicality questionnaire for participants educate. Results study show development material teach worthy for used in the learning process by obtaining an average score of 94.33%. Category worthy of use based on material validator, score 94%, category worthy of use based on the teaching material design validator and a score of 98%, the category is suitable for use, based on the language validator the score is 91%. The research results also show the ingredientsteach worthy used based on value obtained from the results test practicality and response educator with mark average 98.04% category suitable for use.